2016
DOI: 10.1021/acsmedchemlett.6b00188
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AZD2716: A Novel Secreted Phospholipase A2 (sPLA2) Inhibitor for the Treatment of Coronary Artery Disease

Abstract: Expedited structure-based optimization of the initial fragment hit led to the design of ()- (AZD2716) a novel, potent secreted phospholipase A (sPLA) inhibitor with excellent preclinical pharmacokinetic properties across species, clear efficacy, and minimized safety risk. Based on accumulated profiling data, ()- was selected as a clinical candidate for the treatment of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
1
29
0
2
Order By: Relevance
“…To investigate the binding mode of the synthesised inhibitors to different enzyme targets, molecular modelling techniques were deployed using the co-crystal structure of hG-X sPLA2 with the hit compound 1 reported by Giordanetto et al. 38 . In this co-crystal structure, the 4-benzylphenyl moiety of the inhibitor occupies a hydrophobic pocket, while the amide group coordinates with the catalytic site calcium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the binding mode of the synthesised inhibitors to different enzyme targets, molecular modelling techniques were deployed using the co-crystal structure of hG-X sPLA2 with the hit compound 1 reported by Giordanetto et al. 38 . In this co-crystal structure, the 4-benzylphenyl moiety of the inhibitor occupies a hydrophobic pocket, while the amide group coordinates with the catalytic site calcium.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrazine nitrogen forms a critical coordination bond with the calcium ion present as a cofactor for the enzyme, similar to that of the amide moiety of the co-crystallised inhibitor. This interaction plays a central role in the inhibition of PLA2 activity 38 . The 3-methoxyphenyl moiety of 3f occupies the same hydrophobic pocket occupied by the 4-benzylphenyl moiety of the co-crystallised inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“… 23 We identified saturated LPC (LPC18:0) as the main LPC species present in the advanced atherosclerotic lesions, confirming the previous findings that showed the presence and the enzymatic activity of secretory phospholipase A2 in human lesions. 24 LPC associated with plasma lipoproteins accumulating in lesions can be another source of local LPC species. 25 LPA has been reported by others to be significantly higher in coronary than in peripheral systemic arterial blood.…”
Section: Discussionmentioning
confidence: 99%
“…These mutants reflect the different clinical manifestations and pharmacological action of tyrosine kinase inhibitors. In order to explore the possibility of the identified phytocompounds for multi-targeted therapy of NSCLC, the docking calculations were carried out with other proven drug targets with the chain A of HER2, ALK and sPLA2-IIA (PDB Id: 3PP0, Resolution: 2.25 Å, PDB Id: 4Z55, Resolution: 1.55 Å and PDB Id: 5G3N, Resolution: 3.526 Å respectively) ( Aertgeerts et al, 2011 , Michellys et al, 2016 , Giordanetto et al, 2016 ). Since our interest is to study the binding of identified phytocompounds with the catalytic domain of EML4-ALK, we have utilized the structure of the catalytic domain of ALK for the docking studies, given that the experimental structure of fusion protein of EML4-ALK is not available yet and the catalytic domain is identical in both EML4-ALK and ALK.…”
Section: Methodsmentioning
confidence: 99%